Integrated farming system for more produce and higher gains - Singh, R K; Tripathi, Uttam Kumar (Indian Farming, 2020)
The article details the success achieved through the adoption of integrated farming system in District Panna, Madhya Pradesh. The harvest (crop yield) was 32-35% more, net income increased besides additional employment (man days per year) as compared to the traditional practices.